Problematika Guru PAI (Pendidikan Agama Islam) dalam Mengatasi Kenakalan Siswa di SMP Negeri 2 Salang - Oktavia, Reti; Masri, Dedi; Albina, Meyniar (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the problems faced by Islamic Religious Education (PAI) teachers in overcoming student delinquency and the strategies implemented to address such behavior at SMP Negeri 2 Salang. This research employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation. The research informants consisted of PAI teachers, homeroom teachers, and ninth-grade students. The findings reveal that the main challenges faced by PAI teachers include low student learning motivation, weak religious awareness, negative peer influence, and limited variation in teaching methods. The strategies applied by PAI teachers include persuasive-educational approaches, exemplary behavior, habituation of religious values, and collaboration between schools and parents. These strategies have been shown to positively contribute to reducing student delinquency and enhancing students’ moral and religious awareness.